Prabaltiškasis intarpinių ir sta-kamienių veiksmažodžių sluoksnis - Pakalniškienė, Dalia (Baltistica, 1995)
THE PROTO-BALTIC LAYER OF INFIX AND sta-STEM VERBSInfix verbs can be found in almost all Indo-European languages. Some of them might be classified as Proto-Indo-European, e. g. Skr. riṇákti: Lith. liñka: Pr. polinka: Lat. linquo etc. In later stages the evolution of the infix verbs in I.E. languages varied: in some of them these verbs became extinct, in others they grew in number, esp. in the Eastern Baltic languages, where the infix (as well as the suffix sta) has acquired definite functions, non-existent in other I.E. languages.In the formation of the infix and sta-stem verbs in the Eastern Baltic languages categorical semantics played an important role. The origin of the new meaning of spontaneous action is related to the formation of the diathetic oppositional pairs of verbs: part of roots with a vowel change differentiated according to the diathesis. The main roots signified an action performed by an active agent, and the reduced roots – a spontaneous passive action, cf. Balt. *wert-/ *wirt- > Lith. ver̃čia / vir̃sta. 172 oppositions of this type have been recorded in the Lithuanian language, and 67 in the Latvian language.In the epoch of the Eastern Balts some other changes have taken place as well: next to the infix, the sta-stem became established; phonetical possibilities of the infix and sta-stem verbs have expanded: in the position of the final consonant of the root not only explosives (like in other I.E. languages), but also fricatives and sonorants appeared.
Keywords: sta-kamienas; veiksmažodis; intarpinis